Development of a Clinical Pathway and Technical Aspects of Upper Airway Stimulation Therapy for Obstructive Sleep Apnea - Vanderveken, Olivier M.; Beyers, Jolien; Op de Beeck, Sara; Dieltjens, Marijke; Willemen, Marc; Verbraecken, Johan A.; De Backer, Wilfried A.; Van de Heyning, Paul H. (Frontiers in Neuroscience, 2017)
Obstructive sleep apnea (OSA) is a common disease with high morbidity and related mortality. Narrowing and collapse of the pharyngeal airway during sleep characterize the disease, resulting in a decrease (hypopnea) or a complete cessation (apnea) of oronasal airflow. Upper airway stimulation (UAS), using electrical neurostimulation of the hypoglossal nerve (n. XII) synchronized with ventilation, is a novel, evolving treatment option. UAS was found to be an effective treatment in CPAP-intolerant patients. The treatment success is partly due to the strict selection of the patients, based on previous findings. Furthermore, post operative follow-up is needed in order to maintain or improve treatment outcome. Therefore, a clinical pathway, which provides structure and standardization, is crucial. In this paper, the aim is to discuss the technical aspects of UAS therapy and to describe a clinical pathway to organize the care process of UAS for OSA in a structured and standardized way.